Sleep quality status, anxiety, and depression status of nurses in infectious disease department - Xi, Shuangmei; Gu, Yanmei; Guo, Huimin; Jin, Boxun; Guo, Fengjuan; Miao, Wenjing; Zhang, Lili (Frontiers in Psychology, 2022)
Objective: To investigate the current status of sleep quality and influencing factors of clinical nurses in infectious disease hospitals, and to provide basis and reference for improving their sleep status and providing psychological support. Methods: Using convenience sampling method, clinical nurses from a tertiary hospital for infectious diseases were selected as the survey subjects in September 2021. General information questionnaire, Pittsburgh Sleep Quality Questionnaire (PSQI), Generalized Anxiety Disorder Scale (GAD-7), Depression Screening Scale (PHQ-9) were used for questionnaire surveys, and multiple linear regression was used to analyze the impact of insomnia in clinical nurses factor. Results: A total of 460 questionnaires were returned, of which 442 were valid, effective rate is 96.09%. The PSQI score of 442 clinical nurses was 7.07 ± 2.14, of which 60 (13.57%) had sleep disorders; the GAD-7 score was 4.77 ± 3.50, of which 182 (41.18%) had varying degrees of anxiety;The score of PHQ-9 was 5.95 ± 3.79, of which 187 (42.31%) had different degrees of depressive symptoms. The stepwise multiple linear regression analysis which involved PHQ-9 and GAD-7 scores showed that: both the PHQ-9 score and the GAD-7 score were positively correlated with the sleep quality score, and the PHQ-9 score increased every time 1 point, sleep quality score increased by 0.239 points; GAD-7 score increased by 1 point, sleep quality score increased by 0.150 points. The overall model test (F = 109.760, P < 0.001) regression model is meaningful. Conclusion: Insomnia is common among clinical nurses in infectious disease hospitals, and the sleep status of nurses is positively correlated with anxiety and depression. Nursing managers pay attention to the insomnia of clinical nurses in infectious disease hospitals and carry out effective interventions to improve the sleep quality of nurses.